Test and evaluation project no. 28: anti-icing technology, field evaluation report. - Ketcham, Stephen A. (Stephen Alan); Minsk, L. D.; Danyluk, L. S. (1998)
Federal Highway Administration, Office of Engineering Research and Development, McLean, Va. Mode of access: Internet. Author corporate affiliation: Cold Regions Research and Engineering Laboratory, Hanover, N.H. Subject code: BM Subject code: IM Subject code: LKML Subject code: MAH Subject code: SCE Subject code: WW*IJ